Three consequences of the 2012 general elections - Daniel Buti (Sfera Politicii, 2013)
The article represents an analysis of the 2012 general elections and their consequences on the Romanian political system. The variables analysed in the study are: the effective number of parties (N), the level of electoral disproportionality (G) and the nature of bicameralism. Although measured indicators appear to call for an institutional approach and a formal analysis, the article tries to capture and simultaneously takes into account the functional dimension of the political system too. Thus, the consequences of the 2012 parliamentary elections reveal not necessarily the imbalance in the party system or the improvisation of a delegitimized electoral formula, but rather the current makeshift relationships between actors.